Can a teacher-led RCT improve adolescent girls' physical self-perception and perceived motor competence?. Issue 4 (16th February 2019) - Lander, Natalie; Mergen, Judith; Morgan, Philip J.; Salmon, Jo; Barnett, Lisa M.
ABSTRACT: Perceived and actual motor competence (MC) influence physical activity (PA) behaviour. Notably, both are lower in girls than in boys. This study aimed to investigate (i) whether a 12-week, teacher-led intervention that improves actual MC (Lander, N., Morgan, P. J., Salmon, J., & Barnett, L. M. (2017). Improving early-adolescent girls' motor skill: A cluster randomized controlled trial. Medicine and Science in Sports and Exercise. 49 (12), 2498–2505) could also improve adolescent girls' physical self-perception and perceived MC, and (ii) whether change in actual MC is associated with post-intervention perceptions A randomized controlled trial with 171 girls (mean age 12.48 ± 0.34 years), measured perception (i.e., physical self-perception profile (PSPP) and pictorial scale of perceived movement skill competence (PMSC)) and actual MC (i.e., Victorian FMS Teachers' Assessment Manual). Mixed models with post-intervention perception as the outcome, adjusting for baseline perception, group, and change in actual MC, as well as clustering, were performed. An interaction term between change in MC and intervention status was included to test the secondary aim. There were significant intervention effects on girls' physical self-perception as well as their perceived MC. However, there was no association between change in actual MC across the intervention and post intervention perception. While the intervention improved both actual MC and perceived MC, they were not associated.